Mapping the Landscape of Robotics for Autism Spectrum Disorder: A Scoping Review of Technologies, Applications, and Future Directions - Santos, Luiziane Paulino dos; Paradeda, Raul Benites (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2025: Anais da XXXV Brazilian Conference on Intelligent Systems, 2025)
This scoping review explores the use of robotic technologies as intervention tools for children with Autism Spectrum Disorder (ASD), an area of growing interdisciplinary interest. Following the PRISMA-ScR guidelines, we conducted a comprehensive search in the Scopus, IEEE Xplore, and ACM Digital Library databases for studies published between 2018 and 2025. From an initial set of 1167 publications, 27 articles met the inclusion criteria and were analyzed in detail. The results demonstrate a diverse range of robotic applications, with the NAO robot featured in 13 out of the 27 selected studies. Robotics interventions were primarily implemented in assistive therapy, social skills training, educational settings, and joint attention initiatives, predominantly targeting children aged 5 to 10 years. The volume of relevant publications peaked in 2020 and declined in subsequent years, highlighting both increased early momentum and the current need for renewed research efforts in this domain. Overall, the review identifies critical research gaps, particularly in terms of personalized and interdisciplinary intervention approaches. While robotic technologies show considerable promise in supporting autistic children, further high-quality studies are required to assess their long-term effectiveness and to inform the development of individualized, evidence-based practices.